2013
DOI: 10.1530/eje-12-0960
|View full text |Cite
|
Sign up to set email alerts
|

RAC1b overexpression in papillary thyroid carcinoma: a role to unravel

Abstract: Context: The BRAF V600E mutation is the most frequent genetic alteration in papillary thyroid carcinoma (PTC). In colorectal cancer, BRAF V600E was described to functionally cooperate with RAC1b, a hyperactive splice variant of the small GTPase RAC1, to sustain cell survival. This interplay has never been investigated in PTCs.Objective: We aimed to analyze the expression of RAC1b in PTC and correlate its expression with BRAF V600E mutational status, histopathological features, and clinical outcome. Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…However, tumor cells with up-regulated Rac1b may partially survive this situation and thus greatly aggravate the process of the diseases. Our results support previous reports showing that up-regulated Rac1b can contribute to the tumor progression and metastasis [6,[16][17][18] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, tumor cells with up-regulated Rac1b may partially survive this situation and thus greatly aggravate the process of the diseases. Our results support previous reports showing that up-regulated Rac1b can contribute to the tumor progression and metastasis [6,[16][17][18] .…”
Section: Discussionsupporting
confidence: 93%
“…Apart from its constitutive activity, significantly upregulated Rac1b expression has been reported to be deeply involved in tumorigenesis and the metastasis of colorectal, breast, lung, and thyroid cancers [6,[16][17][18] . Transient overexpression of Rac1b in cultured cells was able to promote cell proliferation [19] .…”
Section: Introductionmentioning
confidence: 99%
“…One particular example is the tumor-related splicing variant Rac1b, an isoform of the signaling GTPase Rac1 (Matos et al 2003), in which a usually skipped exon 3b is retained. The resulting protein isoform Rac1b is overexpressed in a specific subtype of colorectal tumors and required to sustain tumor cell survival (Jordan et al 1999;) but was also reported in breast, lung, and thyroid tumors (Schnelzer et al 2000;Radisky et al 2005;Liu et al 2012;Stallings-Mann et al 2012;Silva et al 2013;Zhou et al 2013). Interestingly, Rac1b was found to be predominantly in the signaling-competent GTP-bound conformation (Schnelzer et al 2000;Matos et al 2003;Fiegen et al 2004;Radisky et al 2005), so that small changes in its expression level yield significant cellular responses.…”
Section: Introductionmentioning
confidence: 98%
“…In this CRC study, RAC1b overexpression constituted a marker of poor prognosis. Interestingly, RAC1b overexpression also correlated with the BRAF-V600E mutation and poor prognosis in 68% of papillary thyroid carcinoma [113]. In contrast, no correlation was reported for RAC1b and BRAF mutation in melanoma cell lines [102].…”
Section: Role Of Rac1b Overexpression In Braf-driven Tumorigenesismentioning
confidence: 96%